(untitled) (Orfeu, 2024)
This article integrates comprehensive research on the structure of Brazilian Popular Music (or MPB, in Portuguese acronym), focusing on aspects of form. The study, which essentially intends to establish a firm basis for a theory on form in popular music, is motivated by the lack of specific literature on the subject. It takes as main references for its formulations concepts and assumptions derived from the so-called Neue Formenlehre. Starting with a group of basic definitions (nominal form, structural layers and levels, S/C relations, and factors for segmentation), the study proposes typologies relating to the ideas of macro and micro forms, focusing especially on this last aspect, to which it is associated the conceptual duality of period and sentence (SCHOENBERG, 1967; CAPLIN, 1998). As a central point for discussion, we propose a more flexible perspective for both concepts, based on the observation of musical practice in the context of MPB. The construction of an analytical model focused on the proposed formulations and its application in four case studies are presented in the last sections of the article.